Pengaruh Kualitas Jasa Sistem Informasi Terhadap Kepuasan Pengguna Komputer di RS.Pantai Indah Kapuk - Sarkosih Sarkosih; Lily Widjaya (Indonesian of Health Information Management Journal (INOHIM), 2015)
AbstrakThe successful development of information systems is not only determined by how the information system can process information very well but is determined also by the suitability of the work environment. User satisfaction is one among the various factors determining the success of information system development. This study aims to determine the effect of the quality of information systems services to the computer user satisfaction in Pantai Indah Kapuk hospitals North Jakarta. The study was conducted with cross-sectional and analytic description of the method by the number of sample of 58 respondents who worked in the Department of Nursing consists of outpatient administration section, administration and sexy infirmary medical records and collected by sampling saturated. Dimensions of service quality information system is the performance, aesthetics, ease of maintenance and repair, uniqueness, reliability, durability, quality and usability appropriate suitability. Dimensional computer user satisfaction is the content or the content, accuracy, format, ease of use and timeliness. Most respondents aged less than 40 years old, female, high school educated, work in the section Administration Outpatient and have service life of over 10 years. The average score of service quality information system 46.64 (± 3.717) and the average computer user satisfaction scores 29.29 (± 2.872). The statistical test shows the influence of the quality of information systems services to the computer user satisfaction in the Department of Nursing (r = 0.608 and p <0.05) and the coefficient of determination 36.97. Improving the quality of information system services will increase user satisfaction computers that improve the quality of service.Keywords: The quality of information systems services, the computer user satisfaction